2012
DOI: 10.1155/2012/272710
|View full text |Cite
|
Sign up to set email alerts
|

The Crude Extract fromPuerariaeFlower Exerts Antiobesity and Antifatty Liver Effects in High-Fat Diet-Induced Obese Mice

Abstract: Kudzu, a leguminous plant, has long been used in folk medicine. In particular, its flowers are used in Japanese and Chinese folk medicine for treating hangovers. We focused on the flower of Kudzu (Puerariae thomsonii), and we previously reported the antiobesity effect of Puerariae thomsonii flower extract (PFE) in humans. In this study, we conducted an animal study to investigate the effect of PFE on visceral fat and hepatic lipid levels in mice with diet-induced obesity. In addition, we focused on gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Liu et al reported that PFE improves cognitive impairment in diabetic mice through the normalisation of acetylcholinesterase (AChE) activity and metabolic abnormalities in the brain [28]. Kamiya et al demonstrated that PFE has anti-fatty liver and antiobesity effects in high-fat diet-induced obese mice by suppressing lipogenesis in the liver, stimulating lipolysis in white adipose tissue, and promoting thermogenesis in brown adipose tissue [29]. However, to the best of our knowledge, no report has demonstrated the effect of PFE on endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that PFE improves cognitive impairment in diabetic mice through the normalisation of acetylcholinesterase (AChE) activity and metabolic abnormalities in the brain [28]. Kamiya et al demonstrated that PFE has anti-fatty liver and antiobesity effects in high-fat diet-induced obese mice by suppressing lipogenesis in the liver, stimulating lipolysis in white adipose tissue, and promoting thermogenesis in brown adipose tissue [29]. However, to the best of our knowledge, no report has demonstrated the effect of PFE on endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported preliminary findings demonstrating the anti-obesity effect of PFE in obese humans ( Kamiya et al, 2011 ). Another clinical study revealed that it reduces visceral fat area with no sexual dimorphism ( Kamiya et al, 2012 ). We also reported that PFE exerts anti-obesity and anti-fatty liver effects in high-fat diet-fed mice.…”
Section: Introductionmentioning
confidence: 99%
“…In China, tea made from dried Kudzu flowers is widely consumed [1], and PFE is consumed as a nutritional supplement for the treatment of hangovers and obesity in Japan. We previously reported that PFE exerts anti-obesity effects in humans and mice fed high-fat diets [2][3][4]. In addition, we also reported that the isoflavone-rich fraction of dietary PFE exhibits anti-obesity effect in mice fed high-fat diets [5].…”
Section: Introductionmentioning
confidence: 85%